Research on the Relationship between the Psychological State and Sports Habits of College Students - Yifang Sun, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Objective: The current study examines the relationship between psychological state and sports habits of college students. Methods: To understand the relationship between psychological state and sports habits of college students, this study uses a questionnaire as the main instrument of data collection along with the mental scale sc-l 90 surveys with a view to assess the statistics of the relationship between sports of different frequencies and the mental health of Chinese college students. The principle of random sampling was used to conduct a survey in the form of a questionnaire’ a total of 9,876 questionnaires were distributed, and 9,185 questionnaires were returned. After screening of the responses received a final total of 8499 valid questionnaires were used for data analysis (5,324 for boys and 3,175 for girls). Results: Sports of different frequencies have different effects in terms of improving the mental health of college students; The activity time is increased to more than 60 minutes each time, the number of activities is increased to 3 times a week, the percentage drops to 5%. The number of mixed projects and activities has been increased to 3 times a week, the percentage dropped to 2.3%. Conclusion: The effect of improving the mental health of college students is positive. Engaging in sports in their daily life has a positive and important role in regulating the mental health of college students